Hothouse orchid [large type] - Woods, Stuart (Woods, Stuart. Holly Barker novel., 2009)
Special Agent Holly Barker returns to her hometown of Orchid Beach, Florida, and faces off against an old nemesis-- the man she brought charges against for sexual harassment, attempted rape, and rape. The army officer in question was acquitted of all charges, and is now Orchid Beach's new police chief. Will Holly return to the CIA? Or will she challenge her old nemesis for control of the Orchid Beach Police Department?